ЛЕКСИЧЕСКИЕ СРЕДСТВА ВЫРАЖЕНИЯ ОППОЗИЦИИ «СВОЙ – ЧУЖОЙ» В РУССКОЯЗЫЧНОЙ ЗАРУБЕЖНОЙ ПРЕССЕ СЛАВЯНСКИХ ГОСУДАРСТВ - Жданова, Ирина (Acta Neophilologica, 2017)
In this article, the opposition of the “own – alien” in the Russian-language press of the Slavic states is considered. The research is based on the hypothesis assuming the presence of the opposition “own-alien” in media texts, which may be due to mass migrations, frequent acts of terrorism, and complicated political relations between states in the modern world. The article presents ways of manifesting the opposition “own – alien” in media texts and discusses the features of the lexical expression of this opposition.